Reduction of breathing artifacts in multifrequency magnetic resonance elastography of the abdomen - Shahryari, Mehrgan; Meyer, Tom; Warmuth, Carsten; Herthum, Helge; Bertalan, Gergely; Tzschatzsch, Heiko; Stencel, Lisa; Lukas, Steffen; Lilaj, Ledia; Braun, Jurgen; Sack, Ingolf (Magnetic Resonance in Medicine, 2021)
Purpose: With abdominal magnetic resonance elastography (MRE) often suffering from breathing artifacts, it is recommended to perform MRE during breath-hold. However, breath-hold acquisition prohibits extended multifrequency MRE examinations and yields inconsistent results when patients cannot hold their breath. The purpose of this work was to analyze free-breathing strategies in multifrequency MRE of abdominal organs. Methods: Abdominal MRE with 30, 40, 50, and 60 Hz vibration frequencies and single-shot, multislice, full wave-field acquisition was performed four times in 11 healthy volunteers: once with multiple breath-holds and three times during free breathing with ungated, gated, and navigated slice adjustment. Shear wave speed maps were generated by tomoelastography inversion. Image registration was applied for correction of intrascan misregistration of image slices. Sharpness of features was quantified by the variance of the Laplacian. Results: Total scan times ranged from 120 seconds for ungated free-breathing MRE to 376 seconds for breath-hold examinations. As expected, free-breathing MRE resulted in larger organ displacements (liver, 4.7 ± 1.5 mm; kidneys, 2.4 ± 2.2 mm; spleen, 3.1 ± 2.4 mm; pancreas, 3.4 ± 1.4 mm) than breath-hold MRE (liver, 0.7 ± 0.2 mm; kidneys, 0.4 ± 0.2 mm; spleen, 0.5 ± 0.2 mm; pancreas, 0.7 ± 0.5 mm). Nonetheless, breathing-related displacement did not affect mean shear wave speed, which was consistent across all protocols (liver, 1.43 ± 0.07 m/s; kidneys, 2.35 ± 0.21 m/s; spleen, 2.02 ± 0.15 m/s; pancreas, 1.39 ± 0.15 m/s). Image registration before inversion improved the quality of free-breathing examinations, yielding no differences in image sharpness to uncorrected breath-hold MRE in most organs (P >.05). Conclusion: Overall, multifrequency MRE is robust to breathing when considering whole-organ values. Respiration-related blurring can readily be corrected using image registration. Consequently, ungated free-breathing MRE combined with image registration is recommended for multifrequency MRE of abdominal organs.
CRIS-Team Scopus Importer:2022-08-03
Keywords: abdomen; breathing artifacts; image registration; multifrequency MRE; navigator; stiffness